2017
DOI: 10.14814/phy2.13315
|View full text |Cite
|
Sign up to set email alerts
|

Hypohydration impairs endurance performance: a blinded study

Abstract: The general scientific consensus is that starting exercise with hypohydration >2% body mass impairs endurance performance/capacity, but most previous studies might be confounded by a lack of subject blinding. This study examined the effect of hypohydration in a single blind manner using combined oral and intragastric rehydration to manipulate hydration status. After familiarization, seven active males (mean ± SD: age 25 ± 2 years, height 1.79 ± 0.07, body mass 78.6 ± 6.2, VO2peak 48 ± 7 mL·kg·min−1) completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 38 publications
(64 reference statements)
1
62
0
2
Order By: Relevance
“…Whilst acute dehydration (James et al, 2017) and energy restriction (James et al 2015) might impair performance, the impairments in thermoregulatory and cardiovascular function caused by hypovolaemia/hyperosmolality (Cheuvront and Kenefick, 2014) are of particular concern, and may exacerbate any negative health effects related to heat exposure used to facilitate weight loss (Casa et al, 2015). This is particularly relevant given that heat exposure has been implicated in a number of the deaths reported in those attempting to make weight (Centers for Disease Control, Prevention, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst acute dehydration (James et al, 2017) and energy restriction (James et al 2015) might impair performance, the impairments in thermoregulatory and cardiovascular function caused by hypovolaemia/hyperosmolality (Cheuvront and Kenefick, 2014) are of particular concern, and may exacerbate any negative health effects related to heat exposure used to facilitate weight loss (Casa et al, 2015). This is particularly relevant given that heat exposure has been implicated in a number of the deaths reported in those attempting to make weight (Centers for Disease Control, Prevention, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the role of fluid intake on exercise performance have not been able to match thirst between euhydrated and hypohydrated trials prior to performance tests. 16,17 In contrast, few investigations have observed performance differences even when thirst was matched by mouth rinsing or water ingestion. 3,15,18 In the present study, subjects during the HYP had lower power output and cycling speed in the second time trial, even when hypohydration was just 1% of bodyweight.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that manipulate hydration status through fluid ingestion are limited by nature of drinking and its effects on subject bias. [12][13][14] Recently, few studies have attempted to blind subjects to their fluid replacement and overall hydration state via nasal/ oral-gastric tubes 15,16 or intravenous saline infusion. 17,18 The former studies administered fluids via gastric infusion and reported that dehydration of 2%-2.5% body mass resulted in impaired performance.…”
Section: Introductionmentioning
confidence: 99%
“…The latest National Athletic Trainers’ Association position statement suggests considering fluid replacement volume based on individual fluid losses to avoid a 2% or higher BM loss [18]; there is currently ongoing debate in the literature whether 2% BM loss inevitably leads to reduced performance, or whether people should follow the dictates of thirst [19]. However, recent results recommend preventing BM losses greater than the commonly accepted cut off of 2%, to optimize fluid replacement, as thirst sensation may be insufficient [20-22]. …”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the optimal fluid replacement protocol to preserve euhydration during exercise is heavily debated. The most commonly referred strategies are as follows: (i) replacing fluid losses in order to avoid a 2% BM loss or (ii) following dictates of thirst [19, 31-33]; nevertheless, drinking to thirst has often been found insufficient to prevent dehydration [21, 34, 35], while fluid loss estimated through BM change was shown to impair endurance performance in a blinded study [22]. To date, the influence that T1DM may exert on thirst perception (i.e., the capacity of stimulating thirst depending on changes in blood osmolality), due to chronic fluctuations in blood glucose and osmolality, has not been fully defined, although high glucose levels increasing blood osmolality are likely to signal for increased thirst sensation [36, 37].…”
Section: Discussionmentioning
confidence: 99%